Origin of fluids discharged from mud volcanoes in SE Iran. (August 2019) - Farhadian Babadi, Mahin; Mehrabi, Behzad; Tassi, Franco; Cabassi, Jacopo; Vaselli, Orlando; Shakeri, Ata; Pecchioni, Elena; Venturi, Stefania; Zelenski, Michael; Chaplygin, Ilya
Abstract: Onshore and offshore mud volcanism in the Makran accretionary prism is related to convergence of the Arabian and Eurasian plates. This study describes the chemical and isotopic composition of hydrocarbon-rich fluids from four active on-shore mud volcanoes located along the Makran coast (southern Iran), namely Borborok, Ain, Napag and Sand Mirsuban (Makran coast, southern Iran), as well as Pirgel mud volcano (SE Iran) that is located between the Taftan and Bazman igneous volcanoes. The main aim was to provide insights into the source region(s) of gases and waters discharged from these systems and the secondary processes controlling their chemical features. The four on-shore mud volcanoes emitted CH4 -dominated gases, with significant concentrations of C2+ alkanes suggesting a dominant thermogenic origin, as confirmed by their δ 13 C–CH4 values. Carbon dioxide was present at relatively low concentrations (0.78–2.33%) with an isotopic signature (δ 13 C-CO2 from −34.2 to −11.1‰ vs. V-PDB) in the range of that typical of thermogenic gases. Hence, the geochemical features of these mud volcanoes point to the occurrence of a deep gas source rich in hydrocarbons, although the occurrence of an exploitable gas reservoir has to be confirmed by geophysical measurements and detailed geostructural surveys. Gas chemistry from Pirgel mud volcano completely differs with respect to that of the previous ones, since the former emits gases dominated by CO2 and showing relatively high R/Ra values (≈1.6), suggesting a significant fluid contribution from the nearby volcanic systems. Moreover, waters from the on-shore mud volcanoes showed a Na-Cl composition, typically associated with mud volcanism, whereas those discharged from Pirgel were Na-HCO3 -type and rich in chemical species typical of hydrothermal fluids such as As. Waters from the on-shore volcanoes were characterized by a strong δ 18 O-positive shift and high B and Li concentrations, likely indicating clay mineral dehydration and long-term water-rock interaction. Such geochemical features were also shown by the waters from Pirgel, where the high concentrations of B and Li were possibly related to volcanic source. Estimated temperatures for the on-shore mud volcanoes estimated using the Mg–Li and Mg-K geothermometers range from 84 to 165 °C, corresponding to 3–7 km depth. Highlights: Mud volcanoes of Iranian Makran zone discharge typical thermogenic gases. Pirgel mud volcano uncommonly emits CO2 -rich gases related to a volcanic source. Waters originated from seawater strongly affected by interaction with mineral phases.